Estimation of local inhomogeneity of multilayer nanostructured ZrN/ZrO₂ coating - Skoblo, T.S.; Romaniuk, S.P.; Belkin, Ye.L.; Maltsev, T.V. (Вопросы атомной науки и техники, 2021)
Multilayer nanostructured ZrN/ZrO₂ coatings were applied to increase the operational resistance of various machinery parts by using vacuum-arc deposition in Bulat-type facility. To describe the structure formation, a new approach based on optical-mathematical method for processing metallographic images is proposed. The structure formation of the multilayer coating with an assessment of the degree of its inhomogeneity and diffusion processes between the layers is studied. For a reliable assessment, the changes in the horizontal and vertical directions of the images with the choice of optimal intervals were comparatively analyzed. It has been found that the most stable results are achieved using 20 and 25 dots (pixels).